Performance of platinum and gold catalysts supported on ceria–zirconia mixed oxide in the oxidation of chlorobenzene - Topka, Pavel; Delaigle, Romain; Kaluža, Luděk; Gaigneaux, Eric M. (Catalysis today, 2015)
•Pt/CeZr and Au/CeZr catalysts tested in chlorobenzene oxidation (100ppm in air).•Efficiency of CeZr significantly improved by introduction of Au and especially Pt.•Catalytic performance increased with increasing noble metal loading.•Platinum catalysts more efficient than gold ones due to superior redox properties.•Lower acidity of Pt catalysts not detrimental for their catalytic performance. Monometallic noble metal catalysts supported on ceria–zirconia mixed oxide were prepared by impregnation and tested in the oxidation of chlorobenzene (100ppm in air). With the pure ceria–zirconia support, 27% conversion was achieved at 400°C and only incomplete oxidation to carbon monoxide was evidenced. The introduction of gold and especially platinum significantly improved the efficiency of the catalyst. The catalytic performance increased with increasing noble metal content. The catalyst with 1wt.% of Pt achieved 97% conversion of chlorobenzene already at 350°C and complete oxidation to CO2 with only traces of by-products was detected. Platinum catalysts were more efficient than gold ones, which was ascribed to their superior redox properties. On the other hand, the lower acidity of platinum catalysts was not detrimental for their catalytic performance.